Determinants of Success in Esports: Personality Traits, Psychological States, Mental Skills, and Psychomotor Abilities - Zubić, Ivana M. (Collection of Papers of the Faculty of Philosophy in Priština, 2026)
Esports represents the fastest-growing competitive discipline in which players engage through video games. The aim of this review is to identify key psychological determinants of success in esports, based on the analysis of available empirical studies. A systematic literature search was conducted in Google Scholar, Scopus, and PsicINFO. Twenty-nine empirical studies published in peer-reviewed journals between 2010 and 2024, available in full text in English, were included. Only studies on professional esports players were considered, irrespective of game genre. Findings indicate that personality traits—particularly extraversion, agreeableness, and openness to experience—are associated with performance outcomes. High-ranked players tend to exhibit lower extraversion and agreeableness, but higher openness compared to lower-ranked peers. Esports athletes face multiple stressors: performance-related (score pressure, critical in-game moments, injuries), team-related (communication, teammates’ errors, antisocial behaviour, criticism), external (audience, coaches, opponents, management), as well as challenges in balancing private life and career, and technical difficulties. Constructive stress management and self-regulation skills are therefore essential. Success in esports further depends on advanced psychological skills such as adaptability, mental toughness, frustration tolerance, emotional regulation, and communication competence. Finally, cognitive and psychomotor abilities were consistently identified as significant contributors to performance.